Arabic manuscripts in the library of the S.O.A.S, University of London - Gacek, Adam (Inter Documentation Co., 1985)
Reproduces over 400 items grouped in 394 entries, and includes, in addition to such traditional Islamic disciplines as Tafsīr, Ḥadīth, Fiqh, etc., works on mathematics, astronomy, medicine, falconry, archery, and military equitation.